Using Mindsets to Boost Health - Herter, Márcia Maurer (2022)
Herter, M. M., Borges, A., Pinto, D. C., Ferreira, M. B., & Mattila, A. S. (2022). Using Mindsets to Boost Health: How Construal Level and Goal Pursuit Shape Health Message Effectiveness on Cessation Behaviors. European Journal Of Marketing, 56(12), 3197-3226. https://doi.org/10.1108/EJM-04-2020-0290. ---%ABS3%---Funding: This paper received partial support from the Management of Information Research Center (MagIC), project UIDB/04152/2020.